A complete thermo–electro–viscoelastic characterization of dielectric elastomers, Part I: Experimental investigations. (December 2021) - Mehnert, Markus; Hossain, Mokarram; Steinmann, Paul
Abstract: Dielectric elastomers are a class of solid polymeric materials that are sufficiently soft to deform under the application of an electric field due to the interaction of quasi-static electric charges. Their potential to undergo large deformations renders them promising candidates for the design of energy harvesters, sensors and soft actuators. For their application however, the influence of additional thermal effects should be taken into account as the base materials frequently show a distinct thermal sensitivity that drastically influences their mechanical response. This contribution presents the results of a wide range of experiments conducted on the popular dielectric elastomer VHB 4905™ under a combination of mechanical, thermal and electric loading scenarios. These experiments are performed in such a way that the obtained results are well suited for the identification of the necessary material parameters appearing in a thermo–electro–viscoelastic constitutive model that will subsequently be presented in the second part of the contribution.